Membran karbon templated silika dari karbon nipah (Nypa fruticans) untuk aplikasi desalinasi air rawa asin [Carbon templated silica membranes from nypa carbon (Nypa fruticans) applied for wetland saline water desalination] - Muthia Elma; Mita Riani Rezki; Mahmud Mahmud; Sunardi Sunardi; Elsa Nadia Pratiwi; Era N R Oktaviana; Siti Fatimah; Aulia Rahma (Jurnal Riset Industri Hasil Hutan, 2020)
Nypa carbon templated into silica matrices is an innovation to enhance inorganic silica membrane robustness. Performance of the membrane will be more  stable during application for desalination process. This research aims to investigate silica-nypa membrane performance for   desalination of wetland saline water. Silica-nypa was fabricated by carbon templated which obtained from nypa fruticans leaves and mixed into silica sol by  sol-gel method. Support membrane was coated into  silica-nypa sol by dip-coater and calcined via rapid thermal processing (RTP) technique. Silica-nypa membrane applied for  wetland saline water desalination via pervaporation. The results showed that silica membrane performed the highest water flux by adding nypa 2.5 wt% calcined at 350°C (1.008 kg m-2h-1). Carbon from nypa offered great effect to silica membrane performance. Furthermore, all membranes had high salt rejection >98%. Therefore, carbon template silica membrane from nypa was successfully fabricated and  applied for wetland saline water desalination.